Photodetectors: Large‐Scale Synthesis of Freestanding Layer‐Structured PbI2 and MAPbI3 Nanosheets for High‐Performance Photodetection (Adv. Mater. 39/2017). Issue 39 (13th October 2017) - Lan, Changyong; Dong, Ruoting; Zhou, Ziyao; Shu, Lei; Li, Dapan; Yip, SenPo; Ho, Johnny C.
Abstract : High‐density, crystalline, and freestanding PbI2 and MAPbI3 nanosheets are synthesized by Johnny C. Ho and co‐workers in article number1702759, on a large scale through the nucleation of microplanes on substrates with a rough surface by manipulating the microenvironment during physical vapor deposition. When configured into photodetectors, they exhibit efficient photodetection with excellent performance in responsivity and detectivity.